ANALISIS SEMIOTIKA PADA METODE FOTOGRAFI EDFAT DALAM PERNIKAHAN TRADISI JAWA - Florina, Ike Desi; Sugiharto, Unggul; Noviani, Putri (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Messages and meanings are always present in the scope of everyday life, from words, symbols to traditions that are passed down from generation to generation. A wedding tradition also contains meaning conveyed to the bride and groom. The presence of wedding photos in is not just capturing sacred moments, but also perpetuating messages in the traditional procession that surrounds them. Through the EDFAT photography method, the researcher aims to dig deeper into the messages and meanings contained in the Javanese wedding tradition. Through the semiotic method, Pierce succeeded in expressing meaning through icons, indexes and symbols in the Javanese wedding tradition which was immortalized with the EDFAT photography method. The result is that the EDFAT method emphasizes 3 (three) meanings of messages in Javanese wedding traditions, namely: (1) Advice to a bride and groom in carrying out the household in the form of responsibility, affection and sincerity; (2) Parental advice to children, regarding the blessing, sincerity of parents and balanced affection; (3) Advice of the bride as a child, with the meaning of filial piety to parents.